Notes on whiteness and privileges (Research, Society and Development, 2023)
This study aims to discuss and reflect on the privileges of whiteness, as well as to discuss whether access to opportunities and privileges are attributed in the same way to all people; investigate the mechanisms that legitimize and perpetuate racial inequalities; problematize the position of the white person in discussions of race relations. This article takes a methodological approach based on a bibliographical review of studies on racial relations, problematizing the lack of studies and the participation and recognition of whiteness in these relations. We conclude that whiteness is, therefore, the representation of white as a universal standard of humanity, the norm, which guarantees white people privileges in society. From this article we could observe that for those who historically possessed power, privileges and racial and social advantages, any claim to social, cultural and political equality is a possible threat to the hegemonic culture of whiteness that occupies and always occupies its place of privilege . It is necessary for white people to reflect that whiteness was constructed as a racial place of superiority, making it necessary to also abolish the conception of being superior, recognizing their privileges and that of their group, criticizing it, and being part of the anti-racist struggle.